Room Loan Information System At Website-Based National University: Room Loan Information System At Website-Based National University - Mohamad Farhan Kantami; Fauziah Fauziah; Novi Dian Nathasia (Jurnal Mantik, 2020)
In each of its link, Technology & Information experienced: speed and equalization in its progress. Use of Sisfomen (Management Information System): In the institution there have been many applications because sure to manage-the process becomes very practical and efficient. Activities of an institution, especially on: educational institutions basic, medium and high, in general need to SISFO for efficiency and effectiveness performance. Lending space is: one of the ways in support in the business pace of a field especially campuses that have some also empty space to be processed into additional opportunities. In doing this loan, students or related parties still need to inquire in the campus schedule directly to come to the provider of the room, this makes students or any related parties who want to borrow space waste a lot of time and also the certainty of whether or not the provider. In addition, lending procedures still use manual processes, this is sometimes in the case of loan transactions that arise as conflicts and errors. Therefore, this application is made by the title: "Information system for lending room at National University based Website".